Hubungan Kadar Kalsium-Fosfat Terhadap Derajat Pruritus dan Kualitas Hidup Pada Pasien Penyakit Ginjal Kronis Yang Menjalani Hemodialisis Di Rumah Sakit Prof. Dr. Chairuddin P. Lubis Universitas Sumatera Utara - Azzuhra Putri Siregar (Pusat Riset dan Inovasi Nasional, 2026)
Background. Chronic kidney disease (CKD) remains a significant global health issue because it often leads to long-term complications that affect patients’ physiological and functional status. One factor that may influence disease progression and symptom burden is the imbalance of calcium and phosphate levels. Objective. This study aims to evaluate the association between calcium–phosphate levels, the severity of pruritus, and the quality of life in CKD patients receiving hemodialysis at Prof. dr. Chairuddin P. Lubis Hospital, Universitas Sumatera Utara, Medan. Methods. A correlational analytic design was employed using the Slovin formula, resulting in 63 respondents selected through a cross-sectional approach. Data were obtained from laboratory findings, medical records, and standardized questionnaires collected between August and October 2025. Results. Most respondents were in the 46–65-year age group (54%), with women representing 55.6% of the sample. A total of 58.7% were unemployed, 31.7% identified as Batak, and 58.7% had completed senior high school. Nearly half of the patients had undergone hemodialysis for more than 36 months (45%), and 62.5% presented with normal calcium–phosphate levels. Moderate pruritus, assessed using the 5D Itch Scale, was the most common category (56.3%), while the KDQOL-36 indicated that 45.3% of patients had a moderate quality of life. Statistical testing revealed a significant association between calcium–phosphate levels and pruritus severity (p = 0.044), as well as quality of life (p = 0.011). Conclusion. Calcium–phosphate balance is significantly related to both pruritus severity and quality of life in CKD patients undergoing hemodialysis at RS CPL USU.